Bioaerogels: promising nanostructured materials in fluid management, healing and regeneration of wounds - Bernardes, Beatriz G. (2021)
Wounds affect one’s quality of life and should be managed on a patient-specific approach, based on the particular healing phase and wound condition. During wound healing, exudate is produced as a natural response towards healing. However, excessive production can be detrimental, representing a challenge for wound management. The design and development of new healing devices and therapeutics with improved performance is a constant demand from the healthcare services. Aerogels can combine high porosity and low density with the adequate fluid interaction and drug loading capacity, to establish hemostasis and promote the healing and regeneration of exudative and chronic wounds. Bio-based aerogels, i.e., those produced from natural polymers, are particularly attractive since they encompass their intrinsic chemical properties and the physical features of their nanostructure. In this work, the emerging research on aerogels for wound treatment is reviewed for the first time. The current scenario and the opportunities provided by aerogels in the form of films, membranes and particles are identified to face current unmet demands in fluid managing and wound healing and regeneration.